Breckinridge Long papers - Long, Breckinridge, 1881-1958.; Long, Breckinridge, 1881-1958.
Correspondence, memoranda, diaries, speeches, writings, reports, notes, newspaper clippings, memorabilia, photographs, and other papers relating primarily to Long's career as third assistant secretary of state under Woodrow Wilson (1917-1920), ambassador to Italy (1933-1936), ambassador on special mission to Argentina, Brazil, and Uruguay (1938), and assistant secretary of state under Franklin D. Roosevelt (1940-1944). Also documents Long's work as secretary for the Missouri Code Commission for the revision of judicial procedure (1914), chairman of the National Jefferson Centennial Committee (1925-1929), in the Democratic Party, and trustee of Princeton University, Princeton, N.J. (1937-1941). Includes drafts of Long's Genesis of the Constitution of the United States of America (1926); papers (1740-1945) of the Blair, Breckinridge, Long, and Preston families; material relating to political campaigns (1908-1944); and an autograph collection (1486-1923).
Correspondents include Newton Diehl Baker, Ray Stannard Baker, Bernard M. Baruch, Desha Breckinridge, Jefferson Caffery, Wilbur J. Carr, Bainbridge Colby, Homer S. Cummings, Josephus Daniels, J. Lionberger Davis, James A. Farley, Carter Glass, Harry Bartow Hawes, W.R. Hollister, Edward Mandell House, Andrieus Aristieus Jones, Michael Kinney, Robert Lansing, W.G. McAdoo, Vance Criswell McCormick, Wilbur W. Marsh, George S. Messersmith, George Fort Milton, Henry Morgenthau, A. Mitchell Palmer, William Phillips, Key Pittman, Frank L. Polk, Franklin D. Roosevelt, Daniel C. Roper, Selden P. Spencer, William Stanley, Herbert Bayard Swope, Frank Abner Thompson, Guy Atwood Thompson, Joseph P. Tumulty, and Woodrow Wilson.
Lawyer, diplomat, and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Index to the autograph collection in container 224 also available in the Library of Congress Manuscript Division.
Keywords: Baker, Newton Diehl, -- 1871-1937 -- Correspondence; Baker, Ray Stannard, -- 1870-1946 -- Correspondence; Baruch, Bernard M. -- 1870-1965 -- Correspondence; Breckinridge, Desha, -- 1867-1935 -- Correspondence; Caffery, Jefferson, -- 1886- -- Correspondence; Carr, Wilbur J. -- 1870-1942 -- Correspondence; Colby, Bainbridge, -- 1869-1950 -- Correspondence; Cummings, Homer S. -- 1870-1956 -- Correspondence; Daniels, Josephus, -- 1862-1948 -- Correspondence; Davis, J. Lionberger -- 1878- -- Correspondence; Farley, James A. -- 1888-1976 -- Correspondence; Glass, Carter, -- 1858-1946 -- Correspondence; Hawes, Harry Bartow, -- 1869-1947 -- Correspondence; Hollister, W. R. -- Correspondence; House, Edward Mandell, -- 1858-1938 -- Correspondence; Jones, Andrieus Aristieus, -- 1862-1927 -- Correspondence; Jefferson, Thomas, -- 1743-1826; Kinney, Michael, -- approximately 1875- -- Correspondence; Lansing, Robert, -- 1864-1928 -- Correspondence; McAdoo, W. G. -- 1863-1941 -- Correspondence; McCormick, Vance Criswell, -- 1872-1946 -- Correspondence; Marsh, Wilbur W. -- Correspondence; Messersmith, George S. -- 1883-1960 -- Correspondence; Milton, George Fort, -- 1894-1955 -- Correspondence; Morgenthau, Henry, -- 1891-1967 -- Correspondence; Palmer, A. Mitchell -- 1872-1936 -- Correspondence; Phillips, William, -- 1878-1968 -- Correspondence; Pittman, Key, -- 1872-1940 -- Correspondence; Polk, Frank L. -- 1871-1943 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945.; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Roper, Daniel C. -- 1867-1943 -- Correspondence; Spencer, Selden P. -- 1862-1925 -- Correspondence; Stanley, William -- Correspondence; Swope, Herbert Bayard, -- 1882-1958 -- Correspondence; Thompson, Frank Abner, -- 1880-1958 -- Correspondence; Thompson, Guy Atwood, -- 1875-1958 -- Correspondence; Tumulty, Joseph P. -- 1879-1954 -- Correspondence; Wilson, Woodrow, -- 1856-1924.; Wilson, Woodrow, -- 1856-1924 -- Correspondence; Blair family; Breckinridge family; Long family; Preston family; United States. -- Department of State; Democratic Party (U.S.); Missouri Code Commission; National Jefferson Centennial Committee; Princeton University; Autographs -- Collections; Diplomatic and consular service, American -- Argentina; Diplomatic and consular service, American -- Brazil; Diplomatic and consular service, American -- Italy; Diplomatic and consular service, American -- Uruguay; Procedure (Law) -- Missouri; Universities and colleges -- New Jersey -- Princeton; Argentina -- Foreign relations -- United States; Brazil -- Foreign relations -- United States; Italy -- Foreign relations -- United States; United States -- Foreign relations -- 20th century